Practitioners’ attitude towards RGP Fitting in Klang Valley area / Nur Akmal Mat Nawi - Mat Nawi, Nur Akmal (2016)
Purpose: Rigid gas permeable (RGP) lens has numerous of benefits compared to soft lens However, the trends of RGP lens prescribing had faced a decrement from a few past decades. This study aimed to address the low prescribing rate of RGP lens in Malaysia with particular focus on the practitioners’ attitude to the RGP fitting. Method: A questionnaires was adopted from Gill et al (2009) modified and validated. Two hundred and fifty questionnaires were distributed to optical practices and hospitals in Klang valley area by post and email. Result: Generally, the percentage of lenses prescribed in a year was 86% soft contact lenses, and 14% RGP lenses. Respondents majorly enjoyed the challenges of RGP fitting mainly because they were confidence of their skills in RGP fitting but they felt that it was time consuming for them to fit RGP lenses. It also found that the initial discomfort felt by patient during fitting did hindered the respondents from fitting RGP lenses. Besides, they agreed that slit lamp and keratometer was enough for a successful fitting but having a corneal topographer would be advantageous. Conclusion: This study have provided an information on the reasoning behind the low prescribing trend of RGP lenses. The low recommendation of RGP lenses also have been found mainly due to the patient’s factor with initial discomfort and adaptation issues. As conclusion, practitioners disagreed that RGP lens were becoming irrelevant but initial discomfort issues and long chair time and adaptation period was a very major issues for them especially in private practices.